Current barriers and recommendations on the diagnosis of transthyretin amyloid cardiomyopathy: a Delphi study - Çavuşoğlu, Yüksel; Başarıcı, İbrahim and Tüfekçioğlu, Omaç and Özpelit, Ebru and Özdemir, Elif and Sivrikoz, İlknur Ak and Altay, Hakan and Değertekin, Muzaffer and Dinçer, İrem and İkitimur, Barış and; eci, Gökhan and; urt, Murat Fani and; lıç, Metin and, Gamze Çapa and; aç, Meral and; hoğlu, Ayşe and; özoğlu, Lale (Frontiers in Cardiovascular Medicine, 2024)
This study has been conducted to investigate the non-invasive diagnostic journey of aTTR-CM patients in Turkiye, identify the challenges and uncertainties on the path to diagnosis from expert physicians' perspectives, and develop recommendations that can be applied in such cases.This three round modified Delphi-method study included 10 cardiologists and 5 nuclear medicine specialists. Two hematologists also shared their expert opinions on the survey results related to hematological tests during a final face-to-face discussion. It was considered a consensus when 80% or more of the panel members marked the "agree/strongly agree" or "disagree/strongly disagree" option.All panelists agreed that aTTR-CM diagnosis could be established by scintigraphy (using either 99mTc-PYP, 99mTc-DPD or 99mTc-HMPD) in a patient with suspected CA without a further investigation if AL amyloidosis is ruled out (by sFLC, SPIE and UPIE) and scintigraphy imaging performed by SPECT or SPECT-CT showed Grade ≥2 myocardial uptake with H/CL ratio of ≥1.5. Cardiology panelists positioned CMR and detailed echocardiographic scoring as last resorts before planning an endomyocardial biopsy in patients with suspected CA whose scintigraphy results were discordant/inconclusive or negative but still carried a high clinical suspicion of aTTR-CM.The diagnostic approach in aTTR-CM should be customized based on the availability of diagnostic tools/methods in each expert clinic to achieve a timely and definitive diagnosis.